Effect of Endosymbiotic Bacteria on Fungal Resistance Toward Heavy Metals - Lupini, Simone; Peña-Bahamonde, Janire; Bonito, Gregory; Rodrigues, Debora F. (Frontiers in Microbiology, 2022)
Most studies on metal removal or tolerance by fungi or bacteria focus on single isolates, without taking into consideration that some fungi in nature may be colonized by endobacteria. To address this knowledge gap, we investigated the tolerance and removal of diverse metals with two fungal species: Linnemannia elongata containing Burkholderia-related endobacteria and Benniella erionia containing Mollicute-related endobacteria. Isogenic lines of both species were generated with antibiotic treatments to remove their respective endobacteria. Experiments involved comparing the isogenic lines and wild type fungi in relation to the minimum inhibitory concentration for the metals, the fungal ability to remove these different metals via atomic adsorption spectroscopy, and the interaction of the metals with specific functional groups of the fungi and fungi-bacteria to determine the role of the bacteria via Fourier transformed infrared (FTIR). Finally, we determined the influence of different metal concentrations, associated with moderate and high fungal growth inhibition, on the presence of the endobacteria inside the fungal mycelium via quantitative real-time PCR. Results showed that the presence of the endosymbiont increased B. erionia resistance to Mn2+ and increased the removal of Fe2+ compared to isogenic lines. The absence of the endosymbiont in L. elongata increased the fungal resistance towards Fe2+ and improved the removal of Fe2+. Furthermore, when the bacterial endosymbiont was present in L. elongata, a decrease in the fungal resistance to Ca2+, Fe2+, and Cr6+was noticeable. In the FTIR analysis, we determined that C-H and C=O were the major functional groups affected by the presence of Cu2+, Mn2+, and Fe2+ for L. elongata and in the presence of Cu2+ and Ca2+ for B. eronia. It is noteworthy that the highest concentration of Pb2+ led to the loss of endobacteria in both L. elongata and B. eronia, while the other metals generally increased the concentration of endosymbionts inside the fungal mycelium. From these results, we concluded that bacterial endosymbionts of fungi can play a fundamental role in fungal resistance to metals. This study provides the first step towards a greater understanding of symbiotic interactions between bacteria and fungi in relation to metal tolerance and remediation.